2022
DOI: 10.1167/jov.22.12.5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the frame effect

Abstract: Probes flashed within a moving frame are dramatically displaced (Özkan, Anstis, ‘t Hart, Wexler, & Cavanagh, 2021; Wong & Mack, 1981). The effect is much larger than that seen on static or moving probes (induced motion, Duncker, 1929; Wallach, Bacon, & Schulman, 1978). These flashed probes are often perceived with the separation they have in frame coordinates—a 100% effect (Özkan et al., 2021). Here, we explore this frame effect on flashed tests with several versions of the standard stimulus. We find that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…We first compare the frame's effect on flashed tests (as in Özkan et al., 2021 ; Cavanagh et al., 2022 ) against its effect on a continuously moving test (as in Wallach et al., 1978 ). The frame is always in repetitive left to right motion ( Figure 1 , top; Movie 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first compare the frame's effect on flashed tests (as in Özkan et al., 2021 ; Cavanagh et al., 2022 ) against its effect on a continuously moving test (as in Wallach et al., 1978 ). The frame is always in repetitive left to right motion ( Figure 1 , top; Movie 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…This earlier literature on frame effects typically examined static ( Duncker, 1929 ) or continuously moving probes ( Wallach, Bacon, & Schulman, 1978 ). Recently, we have shown that moving frames give far larger effects for flashed than for continuous probes ( Özkan, Anstis,’t Hart, Wexler, & Cavanagh, 2021 ; Cavanagh et al., 2022 ). These large effects for flashed tests had previously been reported by Duncker (1929) and Wong and Mack (1981) .…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 This perceived position shift occurs robustly across different visual environments such as apparent motion of a frame (instead of actual motion), whole background shifts instead of a moving frame (i.e., background pattern moving left to right), or 3D frame flipping motion. 7 In all cases, this frame-induced position shift yields a drastic perceptual effect, in some conditions resulting in 100% stabilization: The locations of dots are perceived in the frame’s coordinates as if the frame was not in motion at all. Such dramatic effects of perceived position shifts were taken as evidence that surrounding context (such as a moving frame) may act to stabilize the perception of relative locations during eye movements.…”
Section: Introductionmentioning
confidence: 99%
“…This perceived position shift occurs robustly across different visual environments such as apparent motion of a frame (instead of actual motion), whole background shifts instead of a moving frame (i.e., background pattern moving left to right), or 3D frame flipping motion (Cavanagh et al, 2022). In all cases, this frame-induced position shift yields a drastic perceptual effect, in some conditions resulting in 100% stabilization: The locations of dots were perceived in the frame’s coordinates as if the frame was not in motion at all.…”
Section: Introductionmentioning
confidence: 99%
“…This so-called Frame Induced Position Shift (FIPS) illusion elicits a paradoxical stabilization of a moving object: When a frame is moved left to right and two probe stimuli are flashed inside the frame at the exact same physical location shortly before and after the frame moves, participants report these probes to appear at separate locations that match the distance that the frame traveled (Özkan et al, 2021;Cavanagh 2020). This perceived position shift occurs robustly across different visual environments such as apparent motion of a frame (instead of actual motion), whole background shifts instead of a moving frame (i.e., background pattern moving left to right), or 3D frame flipping motion (Cavanagh et al, 2022). In all cases, this frame-induced position shift yields a drastic perceptual effect, in some conditions resulting in 100% stabilization: The locations of dots were perceived in the frame's coordinates as if the frame was not in motion at all.…”
Section: Introductionmentioning
confidence: 99%